ANALYSIS OF CASES OF DEFORMATION OF THE CYLINDRICAL CORE OF SKYSCRAPERS - Alijonov Isfandiyor Asomiddinovich; Shukurova Karomat Kahramonovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article is devoted to the analysis of cases of deformation of the cylindrical core of skyscrapers. The author, relying on the data of the construction industry, analyzed the problem on the basis of the available scientific literature and studied the existing specific aspects of the analysis of cases of deformation of the cylindrical core of skyscrapers.